Modelling the economic potential of the agricultural sector in the Carpathian region of Ukraine - Volodymyr Maksym; Vasyl Chemerys; Marta Kunytska-Iliash; Viktor Borshchevskyi; Vitalii Dushka (Agricultural and Resource Economics, 2025)
Purpose. The purpose of the study is to assess and forecast the economic potential of the agricultural sector in the Carpathian region of Ukraine based on economic-and-mathematical modelling.